COMMODIFICATION OF THE CULTURAL HERITAGE OF PUNCAK PENULISAN TEMPLE IN SUKAWANA VILLAGE, BANGLI REGENCY - Wira Darma, I Kadek Sudana; Wardi, I Nyoman; Suardiana, I Wayan (E-Journal of Cultural Studies; Vol 16 No 4 (2023): Volume 16 Number 4 November 2023, 2023)
Cultural tourism is the largest industry in the world and the fastest-growing sector. This has caused many cultural heritages in the form of temples to be used as tourist attractions, including the Puncak Penulisan Temple in Sukawana Village. As a result of state intervention and capitalism through tourism, it has resulted in the expansion of functions and transformation of cultural values at Puncak Penulisan Temple. Based on the background of this problem, this research aims to (1) analyze the process of commodification Puncak Penulisan Temple, (2) understand the ideology behind the commodification of Puncak Penulisan Temple, and (3) examine the implications of the commodification of Puncak Penulisan Temple. This research was designed using qualitative methods with a critical cultural studies approach. Data collection was carried out through interviews, observations, and literature studies relevant to the research title. Then the collected data was analyzed using qualitative descriptive analysis. The theories used to analyze research problems are the theory of genetic structuralism (Pierre Bourdieu). The results of the research show that the practice of commodifying the Cultural Heritage of Puncak Penulisan Temple has gone through a long process. This is caused by changes in habits (habitus) such as open attitudes of the community, changes in thought patterns and economic orientation, as well as the potential of the Sukawana Village community in the form of cultural and natural heritage. The commodification process is society's response to the struggle between globalization and capitalism through tourism with society's cultural values. The ideology behind the commodification of the Puncak Penulisan Temple's cultural heritage is the ideology of capitalism and the ideology of preservation. The commodification of Puncak Penulisan Temple's cultural heritage has implications for cultural, economic, and social aspects that influence the lives of the people of Sukawana Village. Keywords : commodification, cultural heritage, ideology, Puncak Penulisan Temple